2016
DOI: 10.1177/0091415016685332
|View full text |Cite
|
Sign up to set email alerts
|

Age Differences in the Effects of Mortality Salience on the Correspondence Bias

Abstract: According to terror management theory, awareness of death affects diverse aspects of human thought and behavior. Studies have shown that older and younger adults differ in how they respond to reminders of their mortality. The present study investigated one hypothesized explanation for these findings: Age-related differences in the tendency to make correspondent inferences. The correspondence bias was assessed in younger and older samples after death-related, negative, or neutral primes. Younger adults displaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Other studies have indicated that death anxiety is related to low self-esteem [2, 29]. Terror management theory (TMT), which is based on work by Becker, posits that humans possess a dual-process system that serves a protective function against human awareness of vulnerability and eventual mortality [30]. TMT further predicts that people who adhere to cultural values are better shielded than others against the potential for anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have indicated that death anxiety is related to low self-esteem [2, 29]. Terror management theory (TMT), which is based on work by Becker, posits that humans possess a dual-process system that serves a protective function against human awareness of vulnerability and eventual mortality [30]. TMT further predicts that people who adhere to cultural values are better shielded than others against the potential for anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…This effect seemed to be moderated by greater executive functioning in older adults (Maxfield, Pyszczynski, Greenberg, Pepin, & Davis, 2012). However, more recent studies seem to suggest that either the effect of age emerges when MS is heightened (Maxfield et al, 2014) or that no difference between younger and older adults can be appreciated (Bevan, Maxfield, & Bultmann, 2014;Maxfield, Pyszczynski, Greenberg, & Bultmann, 2017). To the best of our knowledge, the only study investigating the difference associated with reminders of death in brain responses of younger and older adults (Bluntschli, Maxfield, Grasso, & Kisley, 2018) reported greater event related electroencephalography amplitudes in response to deathrelated than negative words, whereas older adults showed the opposite pattern.…”
Section: A C C E P T E Dmentioning
confidence: 95%
“…Unbeknownst to participants, the letter matrix also included 12 meaningless‐relevant words taken from previous research (Van Tongeren & Green, 2010; e.g., aimless, chance, chaos). This manipulation was modeled on hidden word‐search tasks used by previous research to subtly induce existential threat and elicit defensive responses (Maxfield et al., 2014; Maxfield et al., 2017).…”
Section: Methodsmentioning
confidence: 99%